Spinal NF-kB upregulation contributes to hyperalgesia in a rat model of advanced osteoarthritis. (February 2020) - Li, Yunze; Yang, Yixin; Guo, Jinwan; Guo, Xuejiao; Feng, Zhiying; Zhao, Xuli
Knee osteoarthritis (OA) pain is the most common joint pain. Currently, dysfunction in the central nervous system rather than knee joint degeneration is considered to be the major cause of chronic knee OA pain; however, the underlying mechanism remains unknown. The aim of this study was to explore whether spinal NF-κB plays a critical role in chronic knee OA pain. In this study, we used a model induced by the intra-articular injection of monosodium iodoacetate. Spinal NF-κB and the phosphorylation and activation status of NF-κB p65/RelA (p-p65) were inhibited by the intrathecal injection of the inhibitor pyrrolidine dithiocarbamate in this model. After behavioral assessment, the knee was dissected for histopathology, and the spinal cord was dissected and examined for NF-κB, p-p65, and cytokine expression. Furthermore, the quantity and activity of neurons, astrocytes, and microglial cells and their colocalization with p-p65 in the spinal dorsal horn were investigated. Our findings included the following: (1) histology, the pathological changes in the joints of the knee OA model were basically consistent with knee OA patients; (2) the protein and transcription levels of NF-κB/p65 and p-p65 increased before day 14, appeared to decrease on day 21 and increased again on day 28, and the tendency of weight bearing was similar; (3) on days 21 and 28, the intrathecal injection of pyrrolidine dithiocarbamate markedly prevented the monosodium iodoacetate-induced reduction in the paw withdrawal threshold; (4) real-time polymerase chain reaction demonstrated that the expression of TNF-α and IL-33 was suppressed in the knee OA model by the intrathecal injection of pyrrolidine dithiocarbamate; and (5) immunofluorescence revealed that astrocytes were activated and that p-p65 was mainly increased in astrocytes. Our findings indicate that the spinal NF-κB/p65 pathway in astrocytes modulates neuroimmunity in rat model of intra-articular monosodium iodoacetate-induced advanced OA.